Public universities still the top choice - The, Star (The Star, 2017)
WITH reference to your reports under the heading "Are private universities the way forward?" (Sunday Star, Jan 15), we must humbly disagree. We believe that for most parents, public university education is still the top choice. Although there are some good private universities coming up, in general terms we think that public universities are still offering some of the best courses and educational environment for students.